1978
DOI: 10.1039/f29787400417
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of electron spin resonance spectra due to some B12-dependent enzyme reactions

Abstract: Previous studies by a number of authors have shown that during a number of BI2-dependent enzyme reactions, e.g., catalysis of amin0-2,l -propano1 to propionaldehyde in the presence of ethanolamine ammonia lyase as reported by Babior et al., a very characteristic e.s.r. spectrum is observed. It consists of a broad line at g -2.3 and a pair of lines in the intensity ratio of approximately 2 : 1, split by 7-14 mT, centred about g = 2. Schepler et al. have given a partial explanation for this and four other simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
98
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(109 citation statements)
references
References 2 publications
11
98
0
Order By: Relevance
“…This is perhaps mostly due to the tethering of the nitroxide side chain, provided that the backbone of the helix is fixed. When the interspin distance is very small, the EPR line shape may become complicated due to the short-range interactions such asJ coupling and the magnetic anisotropy (15,24). Despite several attempts to elucidate these matters, it is unclear how they affect the EPR line shape at very short distances in the frozen state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is perhaps mostly due to the tethering of the nitroxide side chain, provided that the backbone of the helix is fixed. When the interspin distance is very small, the EPR line shape may become complicated due to the short-range interactions such asJ coupling and the magnetic anisotropy (15,24). Despite several attempts to elucidate these matters, it is unclear how they affect the EPR line shape at very short distances in the frozen state.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that this method accurately measures the interspin distance in the range of [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] A. The accurate determination of distances in this range may be crucial for the understanding of mechanisms of signal transduction or energy transduction involving subtle structural rearrangements (28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To facilitate visual comparison with the field-swept experimental spectra the values of J, A M , A N , and ANt are discussed below in units of G with the conversion between Hertz and Gauss given by eqs. [2]- [4]. The conversion factor for A N is the same as for A M .…”
Section: Computer Simulationsmentioning
confidence: 98%
“…This approach has been used by many investigators to obtain metrical information on spin-labeled biomolecules (1). Others have studied the closely related problem of metal -organic radical interactions in vitamin BI2-dependent enzyme reactions also seeking metrical information (4,5).…”
Section: Introductionmentioning
confidence: 99%